Effect of natural sugars and an artificial sweetener on Biofilm formation of Candida species - Jayarathna, P.D.T.A.; Wijesinghe, G.K.; Weerasekara, M.M.; Gunasekara, T.D.C.P.; Fernando, S.S.N.; Kottegoda, N. (SLMA 129th Anniversary International Medical Congress, 2016, 2016)
Attached

Introduction As biofilms are ubiquitous life forms, biofilm formation may vary under different nutritional conditions such as fermentable sugars leading to many oral complications including dental caries and periodontal diseases. In the present study we investigated the effect of two different concentrations of sugars and an artificial sweetener on biofilm formation of Candida species. Objectives The aim of the study to investigate the effect of two different concentrations of sugars and an artificial sweetener on biofilm formation of Candida species. Method The growth rates of planktonic cells of C.albicans and C.tropicalis was determined by inoculating 96-well plates with 106 cells/ml of organisms suspended in 5% and 10% sweetening agents supplemented medium and measuring the optical density (OD492) at 2 hour intervals. C.albicans, C.tropicalis and 1:1 mixed species adhesion and Biofilm growth rate assays in the presence of 5% and 10% glucose, sucrose and saccharin were quantified using MTT (3- (4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide) and Crystal Violet (CV). The Biofilm architecture was assessed using Scanning electron microscopy (SEM). Results Highest growth rate of planktonic Candida was observed with 5% glucose regardless of species. No significant growth was observed with 5% and 10% saccharin. While both glucose and sucrose (5% and 10%) showed significant positive effect on adhesion of C.albicans, C.troplicalis and mixed species, 5% saccharin significantly reduced the adhesion of monospecies of C.albicans and C.tropicalis. A maximum Biofilm growth rate was observed with 5% sucrose for all species. While 5% saccharin had no significant effect, 10% saccharin reduced the growth of all three Biofilms. Conclusions 5% saccharin did not promote the adhesion of C. albicans and mixed species, however 10% saccharin promoted the adhesion. Although 10% saccharin promoted the adhesion it did not facilitate the growth of Candida biofilms.